Microbial acetone oxidation in coastal seawater - Dixon, Joanna L.; Beale, Rachael; Sargeant, Stephanie L.; Tarran, Glen A.; Nightingale, Philip D. (Frontiers in Microbiology, 2014)
Acetone is an important oxygenated volatile organic compound in the troposphere where it influences the oxidising capacity of the atmosphere. However, the air-sea flux is not well quantified, in part due to a lack of knowledge regarding which processes control oceanic concentrations, and, specifically whether microbial oxidation to CO2 represents a significant loss process. We demonstrate that 14C labelled acetone can be used to determine microbial oxidation to 14CO2. Linear microbial rates of acetone oxidation to CO2 were observed for between 0.75-3.5 hours at a seasonally eutrophic coastal station located in the western English Channel (L4). A kinetic experiment in summer at station L4 gave a Vmax of 4.1 pmol L-1 h-1, with a Km constant of 54 pM. We then used this technique to obtain microbial acetone loss rates ranging between 1.2-42 pmol L-1 h-1 (monthly averages) over an annual cycle at L4, with maximum rates observed during winter months. The biological turnover time of acetone (in situ concentration divided by microbial oxidation rate) in surface waters varied from ~3 days in February 2011, when in situ concentrations were 3 ± 1 nM, to >240 days in June 2011, when concentrations were more than 2 fold higher at 7.5 ± 0.7 nM. These relatively low marine microbial acetone oxidation rates, when normalised to in situ concentrations, suggest that marine microbes preferentially utilise other oxygenated volatile organic compounds such as methanol and acetaldehyde.